Pengaruh Kemandirian Belajar dan Motivasi Belajar Terhadap Prestasi Belajar Siswa Kelas VIII A SMP Negeri 1 Lakudo - Ernawati Jais; Zul Fahnur (Jurnal Akademik Pendidikan Matematika, 2021)
The formmulation of the problems in this study were: (1) whether independent learning afected the learning achievement of class VIl A students of SMP Negeri 1 Lakudo, (2) whether learning motivation affected the learning achievement of classVIll A students of SMP Negeril Lakudo; and (3) whether independent learning andlearning motivation affected the learning achievement of class VIlI A students of SMPNegeri 1 Lakudo. This stucdy was Er-Post Facto research, which was conducted in class VIll A of SMP Negeril Lakudo, even semester of the 2019 2020 school year. Data collectionim this stucy was carried out using a research instrument in the form of aquestionnaire. Population in this research were l08 students. Sampel in this researchwere 33 students by using random sampling technique. The data obtained were thenamalyzed by descriptive anahsis and inferential analysis and tested the hypothesis inthe form of the t-test. The study results obtained: (1) the minimum and maximum scores of the independent learning questionnaire were 94 and 121, the minimum and maximum Scores of the learning motivation questionnaire were 91 and 136, and the minimum and maximum scores of student learning achie vement were 60 and 83; (2) the mean Score of the learming independence questionnaire was 67, the mean score of thelearning motivation questionnaire was 71 and the student achievement average score was 68; and (3) based on the results of hypothesis testing with t-test, the value of tount 7.867 with a significance value of p = 0.001 was obtained. So that there was asignificant relationship between learning independence and learning motivation onstudents' achievement.